COMPARATIVE LUNG MORPHOLOGY UNDER THE INFLUENCE OF A COMPLEX KETOGENIC DIET IN METABOLIC SYNDROME - Rabimova Z.Sh., Azizova D.M., Rahmonov A.H., Inoyatova F.X. (Central Asian Journal of Medicine, 2025)
The aim of this study was to investigate the effects of high-fat and high-carbohydrate diets on morphological changes in the lungs of rats using a metabolic syndrome model. The study used 40 rats, which were divided into 7 groups. Metabolic syndrome was modeled by feeding them with a 10% fructose solution for 1 and 3 months. Lung tissue from each group was examined histologically at 30, 60, and 90 days. According to the results, an increase in the number of mononuclear immunocytes in rats with metabolic syndrome was observed compared to groups fed with separate diets. It was found that the level of mononuclear infiltration was higher in the group of rats that were modeled with metabolic syndrome for three months without a diet. Also, a deepening of the fibrosis process, thickening of alveolar septa, and a decrease in functional alveolar surface area were observed. This study reliably demonstrated the effect of metabolic syndrome on morphological changes in lung tissue and provided basic data for future pharmacotherapeutic studies.